MATHEMATICAL AND STATISTICAL PROCESSING OF TEST QUALITY USING THE MATLAB SOFTWARE - Abilmazhinova, Б.С.; Baibaktina, А.Т.; Muslimova, А.К. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
This article discusses the quality of test tasks and how it affects the objectivity of students' knowledge assessment. Improving the quality of the test in measuring the knowledge of students in the modern format of blended learning is essential. In the course of the article were considered features of modern theory of test construction, its difference from the classical theory. In general, the process of scientific explanation of test quality can be divided into three steps. The first step is the collection of empirical data, the second - processing of empirical data, and the third - analysis of processing results in order to improve the quality of the test. The main purpose of the article is to determine the quality of the test through the analysis of empirical data, methods to improve it. The goal was achieved by using mathematical and statistical tools and functional capabilities of MatLab. MatLab is an interactive system for technical calculations, visualization and programming. It has a main data element as an array, which allows solving various tasks several times faster than writing programs using programming languages. Statistical analysis was used as the research method. Several tables, diagrams, presented analysis of mid-term results.